A heat shock resistant magnesia-carbon composite refractory brick and its preparation method
Through layered design and the use of modified materials, combined with variable pressure compression technology, the problem of mismatch between oxidation resistance and thermal expansion at high temperatures is solved, which improves the flexural strength, oxidation resistance and thermal shock resistance, and extends the service life.
Patent Information
- Application Number
- CN202510559266.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-07-08
- Estimated Expiration
- 2045-04-30
AI Technical Summary
Existing magnesium-carbon refractory bricks lack oxidation resistance at high temperatures, and mismatch in thermal expansion leads to poor thermal shock resistance, prone to cracks and peeling, affecting service life.
The layered material design is adopted, and modified magnesium sand, zirconium oxide, silicon carbide-doped resin and aluminum titanate fiber are coated with silicon carbide, combined with variable pressure pressing technology to form a three-layer structure refractory brick. The inner layer, intermediate layer and outer layer are proportioned in different proportions, and the B-Si-Al-O glass phase is generated through segmented curing and sintering to enhance flexural strength and oxidation resistance.
It significantly improves the flexural strength, oxidation resistance, thermal shock resistance and expansion resistance of refractory bricks, extends its service life, and adapts to complex industrial conditions at high temperatures.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesia refractory furnace wall materials, and particularly relates to a thermal shock-resistant magnesia-carbon composite refractory brick and a preparation method thereof. Background Art
[0002] In high-temperature industrial fields such as steel smelting and glass manufacturing, refractory materials are key materials to ensure the normal operation of production equipment and the smooth progress of high-temperature processes. In steelmaking equipment such as converters and electric furnaces, refractory materials need to withstand extremely complex and harsh working conditions. On the one hand, during the steelmaking process, the temperature inside the furnace changes rapidly, and the instantaneous temperature fluctuation can reach several hundred degrees. For example, during the blowing period of the converter, the violent reaction between the high-temperature molten steel and the slag will cause the temperature of the furnace lining to rise rapidly, while during the tapping and hot metal charging stages, the temperature will drop rapidly. This frequent and violent thermal shock has posed a great challenge to the structural stability of refractory materials. Refractory bricks with poor performance are extremely prone to cracks, spalling, and even damage due to thermal stress, seriously affecting the service life of the furnace lining and the continuity of steelmaking production. The same is true in the glass manufacturing industry. During the operation of a glass furnace, the temperature is long-term at about 1500 °C, and obvious temperature changes will occur during furnace startup, shutdown, and temperature adjustment during production. The components such as alkaline oxides contained in the glass liquid also have a strong erosion effect on refractory bricks, requiring refractory materials to not only have good thermal shock resistance but also excellent resistance to glass liquid erosion.
[0003] Traditional refractory bricks are difficult to meet these complex and harsh performance requirements simultaneously. Magnesia-carbon refractory bricks use magnesite as the main raw material to provide high melting point and high strength, and carbon materials to enhance their thermal shock resistance and slag erosion resistance. The combination of the two forms unique performance advantages. However, magnesia-carbon refractory bricks still have the following problems in practical applications:
[0004] (1) Insufficient oxidation resistance at high temperatures: The carbon in the magnesia-carbon composite refractory brick is easily oxidized in a high-temperature oxidizing atmosphere, forming pores and defects, resulting in a loose structure of the brick body. This will not only reduce the strength of the brick but also weaken the bonding force between magnesite particles, thereby affecting the thermal shock resistance. In high-temperature oxidizing environments such as steelmaking, the oxidation problem of carbon is relatively prominent, limiting the service life of magnesia-carbon bricks.
[0005] (2) Problem of large thermal expansion: There is a difference in the thermal expansion coefficients of magnesite and carbon. During the rapid temperature change process, this difference will cause thermal stress inside the brick body. When the thermal stress exceeds the bearing capacity of the brick body, cracks or even spalling will occur. Even if the difference is minimized by optimizing the formula and process during production, in actual high-temperature and frequently thermal-shocked working conditions, the thermal expansion mismatch may still cause problems, affecting the stability and service life of the brick body.
[0006] Therefore, it is necessary to continuously research and develop and improve the preparation process, optimize the raw material formula, adopt advanced forming technology and heat treatment process, etc., to further improve its thermal shock resistance while not affecting other service performances, so that it can better adapt to the complex working conditions of high-temperature industries and meet the growing production needs. Summary of the Invention
[0007] Aiming at the problems of insufficient oxidation resistance and poor thermal expansion matching of existing magnesia-carbon refractory bricks at high temperatures, which lead to the influence on thermal shock resistance, easy occurrence of looseness, cracks and spalling, and reduction of service life. The present invention provides a thermal shock-resistant magnesia-carbon composite refractory brick and its preparation method. Through layered batching design, silicon carbide-coated modified magnesia and zirconia, silicon carbide-doped resin, toughening with aluminum titanate fiber and formation of B-Si-Al-O glass phase, and variable pressure pressing designed according to the characteristics of each layer of materials, the flexural strength, oxidation resistance, thermal shock resistance and anti-expansion of the refractory brick are significantly improved. The specific technical solutions are as follows:
[0008] A thermal shock-resistant magnesia-carbon composite refractory brick, the refractory brick includes a three-layer structure, which are the inner layer, the middle layer and the outer layer in sequence, and the thickness ratio is inner layer: middle layer: outer layer = 1: (0.6 - 0.8): (0.8 - 1);
[0009] The base material of the inner layer includes the following raw materials in parts by mass: 60 parts - 65 parts of silicon carbide-coated modified magnesia, 12 parts - 15 parts of flake graphite, 2 parts - 3 parts of silicon powder, 1 part - 2 parts of boron carbide (B4C), 1 part - 1.5 parts of nano-aluminum oxide (Al2O3), 3 parts - 4 parts of aluminum titanate fiber (Al2TiO5), 2 parts - 4 parts of silicon carbide-coated modified zirconia, 6 parts - 8 parts of silicon carbide-doped phenolic resin liquid;
[0010] The base material of the middle layer includes the following raw materials in parts by mass: 70 parts - 75 parts of silicon carbide-coated modified magnesia, 9 parts - 11 parts of flake graphite, 2 parts - 3 parts of silicon powder, 1 part - 2 parts of boron carbide (B4C), 1 part - 1.5 parts of nano-aluminum oxide (Al2O3), 5 parts - 7 parts of zircon powder (ZrSiO4), 3 parts - 4 parts of aluminum titanate fiber (Al2TiO5), 7 parts - 9 parts of silicon carbide-doped phenolic resin liquid;
[0011] The base material of the outer layer includes the following raw materials in parts by mass: 80 parts - 85 parts of silicon carbide-coated modified magnesia, 5 parts - 8 parts of flake graphite, 2 parts - 3 parts of silicon powder, 1 part - 2 parts of boron carbide (B4C), 1 part - 1.5 parts of nano-aluminum oxide (Al2O3), 3 parts - 4 parts of aluminum titanate fiber (Al2TiO5), 7 parts - 9 parts of silicon carbide-doped phenolic resin liquid.
[0012] Further, the preparation method of the silicon carbide-coated and modified magnesite includes the following steps: According to the mass ratio, magnesite: spun asphalt: silicon carbide = 100: (2 - 4): (3 - 6), uniformly mix magnesite and silicon carbide, then add spun asphalt and mix uniformly, and carry out stirring modification at 360°C - 450°C for 2h - 4h, cool, and break up to obtain the silicon carbide-coated and modified magnesite.
[0013] Further, the rotation speed of the stirring modification is 80r / min - 150r / min; the magnesite is dead-burned magnesia, and the calcination temperature of the dead-burned magnesia is 1800°C - 2000°C; the particle size distribution of the magnesite is that the particles with a particle size less than 5mm and greater than or equal to 3mm account for 25wt% - 30wt%, the particles with a particle size less than 3mm and greater than or equal to 1mm account for 35wt% - 40wt%, the particles with a particle size less than 1mm and greater than or equal to 0.5mm account for 30wt% - 35wt%, and the particles with a particle size less than 0.5mm account for 5wt% - 10wt%; the median particle size of the silicon carbide is below 5μm; the median particle size of the spun asphalt is below 2μm.
[0014] Further, the preparation method of the silicon carbide-coated and modified zirconia includes the following steps: According to the mass ratio, zirconia: spun asphalt: silicon carbide = 100: (3 - 5): (5 - 8), uniformly mix zirconia and silicon carbide, then add spun asphalt and mix uniformly, and carry out stirring modification at 360°C - 450°C for 2h - 4h, cool, and break up to obtain the silicon carbide-coated and modified zirconia.
[0015] Further, the rotation speed of the stirring modification is 100r / min - 200r / min; the median particle size of the zirconia is 20μm - 30μm; the median particle size of the silicon carbide is below 5μm; the median particle size of the spun asphalt is below 2μm.
[0016] Further, the mass ratio of the silicon carbide admixed with phenolic resin liquid is phenolic resin liquid: silicon carbide = 100: (6 - 10); the median particle size of the silicon carbide is 30μm - 60μm.
[0017] Further, the median particle sizes of the flake graphite, silicon powder, and boron carbide are all below 20μm; the particle size of the nano-aluminum oxide is below 200nm; the diameter range of the aluminum titanate fiber is 5μm - 15μm, and the length range is 50μm - 200μm; the median particle size of the zircon powder is 2μm - 6μm.
[0018] The preparation method of the above heat shock resistant magnesia-carbon composite refractory brick includes the following steps:
[0019] S1, Batching: According to the mass parts, respectively mix and prepare the base materials for the inner layer, the middle layer and the outer layer;
[0020] S2, Pressing: First, fill the base material of the inner layer into the mold and carry out layer-by-layer filling and pressing. The die head pressure is 260 MPa - 280 MPa. After reaching the thickness of the inner layer, replace the filler with the base material of the middle layer and continue layer-by-layer filling and pressing. The die head pressure is 230 MPa - 250 MPa. After reaching the thickness of the middle layer, replace the filler with the base material of the outer layer and continue layer-by-layer filling and pressing. The die head pressure is 200 MPa - 230 MPa. After reaching the thickness of the brick body, keep the pressure and end the pressing to obtain a brick blank;
[0021] S3, Segmented Curing and Sintering: Cure the brick blank at 180°C - 250°C for 12 h - 14 h, then heat up to 600°C - 700°C for carbonization for 4 h - 5 h, and then heat up to 1450°C - 1550°C for sintering reaction for 2 h - 2.5 h to promote the formation of a dense B-Si-Al-O glass phase of Si + B4C + Al2O3; Cool to obtain a refractory brick.
[0022] Further, in S2, the pressure for keeping the pressure is 200 MPa - 230 MPa, and the time for keeping the pressure is 5 min - 10 min.
[0023] Further, in S3, the heating rate is 2°C / min - 4°C / min.
[0024] When the above heat shock resistant magnesia-carbon composite refractory brick is used for lining a furnace, the inner layer of the refractory brick faces the furnace cavity, and the outer layer of the refractory brick faces the furnace outer wall.
[0025] A heat shock resistant magnesia-carbon composite refractory brick and its preparation method provided by the present invention, compared with the prior art, have the following beneficial effects:
[0026] I. Inner layer: Silicon carbide-coated modified magnesia provides high melting point and strength, flake graphite enhances heat shock resistance and slag erosion resistance, silicon powder, boron carbide, etc. can form a dense phase to improve oxidation resistance, etc. Aluminum titanate fiber can relieve thermal expansion, and silicon carbide-coated modified zirconia can stabilize the structure, overall improving heat shock resistance and other properties. Middle layer: More silicon carbide-coated modified magnesia ensures strength, zircon powder improves erosion resistance and heat shock resistance, and cooperates with other components to enhance the overall performance, playing a role of transition and strengthening.
[0027] Outer layer: A high proportion of silicon carbide-coated modified magnesite enhances the structural strength, and less flake graphite reduces the oxidation risk, focusing on improving oxidation resistance, thermal shock resistance, and reducing costs. Among the layers, silicon powder, boron carbide, and nano-aluminum oxide react at high temperatures to form a B-Si-Al-O glass phase, dynamically sealing the pores and inhibiting oxygen penetration, thereby providing oxidation resistance. Aluminum titanate fibers are interspersed in the matrix, and their negative thermal expansion characteristics are used to offset the expansion of magnesite, reducing the overall thermal expansion coefficient. The three layers cooperate with each other to improve the overall thermal shock resistance, flexural strength, oxidation resistance, and anti-expansion performance.
[0028] Second, the silicon carbide coating layer can relieve the thermal stress concentration of magnesite particles during temperature changes. Moreover, silicon carbide has a high thermal conductivity, which can quickly conduct heat, reduce the temperature gradient, and improve heat resistance. Silicon carbide increases the bonding force between magnesite particles, enhances the overall structural strength, and makes it more difficult to break when resisting external forces. The silicon carbide coating layer isolates the contact between magnesite and oxygen, reducing the chance of magnesite being oxidized. The thermal expansion coefficient of silicon carbide has a certain match with that of magnesite, reducing the overall thermal expansion difference.
[0029] Third, the silicon carbide coating can buffer the volume change of zirconia during thermal shock, inhibiting crack generation and propagation. The coating layer enhances the bonding force between zirconia and other components, improves the overall structural stability, and increases the flexural strength. Silicon carbide prevents oxygen from contacting zirconia, reducing the possibility of zirconia being oxidized at high temperatures and avoiding the possibility of reaction with the contacting materials. Silicon carbide can regulate the thermal expansion behavior of zirconia to better match it with the surrounding materials.
[0030] Fourth, the high thermal conductivity of silicon carbide makes the heat transfer of phenolic resin liquid more uniform during temperature changes, reducing thermal stress. Silicon carbide particles are filled in the phenolic resin liquid, playing a role in strengthening the skeleton and improving the flexural strength. To a certain extent, silicon carbide can isolate the contact between oxygen and phenolic resin liquid, slowing down oxidation. Silicon carbide can limit the expansion of phenolic resin liquid when heated, making the overall expansion more uniform. Pre-dispersed silicon carbide in the resin forms a SiC-carbon composite bonding phase after curing, enhancing the heat resistance.
[0031] Fifth, in the preparation method, variable pressure pressing is designed. A large inner layer pressure is conducive to forming a dense structure, improving the erosion resistance in contact with the material; a moderate middle layer pressure ensures the structure and performance of the transition layer; a smaller outer layer pressure prevents the outer layer from being too dense, resulting in excessive internal stress, and at the same time can form a certain density to provide oxidation resistance. Variable pressure pressing optimizes the structure and performance of each layer, improving the overall performance.
[0032] VI. In the preparation method, curing is carried out first, followed by carbonization, and finally high-temperature sintering. Curing preliminarily crosslinks the resin to form a certain network structure. The carbonization process further enhances the structural stability. Sintering enables the components to react to form a dense phase, improving the thermal shock resistance. The structure formed by curing and carbonization provides a stable foundation for sintering. Sintering makes the components combine more tightly, improving the flexural strength. The curing and carbonization processes can form a certain protective layer on the surface of the brick body. The dense phase formed by sintering further prevents oxygen from entering, improving the oxidation resistance. The step-by-step treatment gradually optimizes the internal structure of the material, reduces the uneven thermal expansion and internal stress caused by rapid sintering, and improves the anti-expansion property.
[0033] In summary, through layered design, silicon carbide-coated modified magnesite and zirconia, silicon carbide-doped phenolic resin, toughening with aluminum titanate fibers, and the formation of a B-Si-Al-O glass phase, and by designing variable-pressure pressing according to the material properties of each layer, the present invention significantly improves the flexural strength, oxidation resistance, thermal shock resistance, and anti-expansion of refractory bricks, having good practical value. Specific Embodiments
[0034] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to these embodiments.
[0035] Example 1: A magnesia-carbon composite refractory brick with thermal shock resistance. The refractory brick includes a three-layer structure, namely an inner layer, a middle layer, and an outer layer, and the thickness ratio is inner layer: middle layer: outer layer = 1:0.7:0.9;
[0036] The base material of the inner layer includes the following raw materials in parts by mass: 62 parts of silicon carbide-coated modified magnesite, 13.5 parts of flake graphite, 2.5 parts of silicon powder, 1.5 parts of boron carbide (B4C), 1.2 parts of nano-aluminum oxide (Al2O3), 3.5 parts of aluminum titanate fiber (Al2TiO5), 3 parts of silicon carbide-coated modified zirconia, and 7 parts of silicon carbide-doped phenolic resin liquid;
[0037] The base material of the middle layer includes the following raw materials in parts by mass: 73 parts of silicon carbide-coated modified magnesite, 10 parts of flake graphite, 2.5 parts of silicon powder, 1.5 parts of boron carbide (B4C), 1.2 parts of nano-aluminum oxide (Al2O3), 6 parts of zirconium silicate micropowder (ZrSiO4), 3.5 parts of aluminum titanate fiber (Al2TiO5), and 8 parts of silicon carbide-doped phenolic resin liquid;
[0038] The base material of the outer layer includes the following raw materials in parts by mass: 82 parts of silicon carbide-coated modified magnesite, 6.5 parts of flake graphite, 2.5 parts of silicon powder, 1.5 parts of boron carbide (B4C), 1.2 parts of nano-aluminum oxide (Al2O3), 3.5 parts of aluminum titanate fiber (Al2TiO5), and 8 parts of silicon carbide-doped phenolic resin liquid.
[0039] Among them, the preparation method of silicon carbide-coated and modified magnesite includes the following steps: Select dead-burned magnesia with a calcination temperature of 1800 °C as magnesite and conduct particle size grading: particles with a particle size less than 5 mm and greater than or equal to 3 mm account for 30 wt%, particles with a particle size less than 3 mm and greater than or equal to 1 mm account for 35 wt%, particles with a particle size less than 1 mm and greater than or equal to 0.5 mm account for 30 wt%, and particles with a particle size less than 0.5 mm account for 5 wt%; Crush silicon carbide to obtain a powder with a median particle size of 3.2 μm; Crush spinning pitch to obtain a powder with a median particle size of 1.6 μm. By mass ratio, magnesite:spinning pitch:silicon carbide = 100:3:5. Uniformly mix magnesite and silicon carbide, and then add spinning pitch for uniform mixing. Stir and modify at 400 °C and a rotation speed of 120 r / min for 3 h, cool, and break up to obtain silicon carbide-coated and modified magnesite.
[0040] Among them, the preparation method of silicon carbide-coated and modified zirconia includes the following steps: Crush zirconia to obtain a powder with a median particle size of 26.5 μm; Use the crushed silicon carbide in the preparation method of the above-mentioned silicon carbide-coated and modified magnesite for silicon carbide; Use the crushed spinning pitch in the preparation method of the above-mentioned silicon carbide-coated and modified magnesite for spinning pitch. By mass ratio, zirconia:spinning pitch:silicon carbide = 100:4:6.5. Uniformly mix zirconia and silicon carbide, and then add spinning pitch for uniform mixing. Stir and modify at 400 °C and a rotation speed of 150 r / min for 3 h, cool, and break up to obtain silicon carbide-coated and modified zirconia.
[0041] Among them, the mass ratio of silicon carbide admixed with phenolic resin liquid is phenolic resin liquid:silicon carbide = 100:8; The median particle size of silicon carbide is 42.7 μm. The median particle size of flake graphite is 15.2 μm. The median particle size of silicon powder is 16.4 μm. The median particle size of boron carbide is 14.3 μm. The particle size range of nano-aluminum oxide is below 200 nm. The diameter range of aluminum titanate fiber is 5 μm to 15 μm, and the length range is 50 μm to 200 μm. The median particle size of zircon powder is 4.2 μm.
[0042] The above preparation method of a thermal shock-resistant magnesia-carbon composite refractory brick includes the following steps:
[0043] S1, batching: Mix and prepare the base materials for the inner layer, the middle layer, and the outer layer respectively according to mass parts;
[0044] S2, Pressing: First, fill the inner base material into the mold and perform layer-by-layer pressing. The die head pressure is 270 MPa. After reaching the inner layer thickness, replace the filler with the base material of the middle layer and continue layer-by-layer pressing. The die head pressure is 240 MPa. After reaching the middle layer thickness, replace the filler with the base material of the outer layer and continue layer-by-layer pressing. The die head pressure is 220 MPa. After reaching the brick body thickness, maintain the pressure at 220 MPa for 8 minutes to end the pressing and obtain a brick blank.
[0045] S3, Segmented Curing and Sintering: Cure the brick blank at 220 °C for 13 h, then heat it up to 650 °C at a rate of 3 °C / min for carbonization for 4.5 h, and then heat it up to 1500 °C at a rate of 3 °C / min for sintering reaction for 2 h to promote the formation of a dense B-Si-Al-O glass phase of Si + B4C + Al2O3; cool to obtain a refractory brick.
[0046] Example 2: A thermal shock-resistant magnesia-carbon composite refractory brick, the refractory brick includes a three-layer structure, namely an inner layer, a middle layer and an outer layer, and the thickness ratio is inner layer: middle layer: outer layer = 1:0.6:0.8;
[0047] The base material of the inner layer includes the following raw materials in parts by mass: 60 parts of silicon carbide-coated modified magnesia, 12 parts of flake graphite, 2 parts of silicon powder, 1 part of boron carbide (B4C), 1 part of nano-aluminum oxide (Al2O3), 3 parts of aluminum titanate fiber (Al2TiO5), 2 parts of silicon carbide-coated modified zirconia, 6 parts of silicon carbide-doped phenolic resin solution;
[0048] The base material of the middle layer includes the following raw materials in parts by mass: 70 parts of silicon carbide-coated modified magnesia, 9 parts of flake graphite, 2 parts of silicon powder, 1 part of boron carbide (B4C), 1 part of nano-aluminum oxide (Al2O3), 5 parts of zircon powder (ZrSiO4), 3 parts of aluminum titanate fiber (Al2TiO5), 7 parts of silicon carbide-doped phenolic resin solution;
[0049] The base material of the outer layer includes the following raw materials in parts by mass: 80 parts of silicon carbide-coated modified magnesia, 5 parts of flake graphite, 2 parts of silicon powder, 1 part of boron carbide (B4C), 1 part of nano-aluminum oxide (Al2O3), 3 parts of aluminum titanate fiber (Al2TiO5), 7 parts of silicon carbide-doped phenolic resin solution.
[0050] Among them, the preparation method of silicon carbide-coated modified magnesite includes the following steps: Select dead-burned magnesia with a calcination temperature of 1800°C as magnesite, and conduct particle size grading: particles with a particle size less than 5 mm and greater than or equal to 3 mm account for 25 wt%, particles with a particle size less than 3 mm and greater than or equal to 1 mm account for 40 wt%, particles with a particle size less than 1 mm and greater than or equal to 0.5 mm account for 30 wt%, and particles with a particle size less than 0.5 mm account for 5 wt%; Crush silicon carbide to obtain a powder with a median particle size of 2.7 μm; Crush spinning pitch to obtain a powder with a median particle size of 1.2 μm. By mass ratio, magnesite:spinning pitch:silicon carbide = 100:2:3. Uniformly mix magnesite and silicon carbide, and then add spinning pitch for uniform mixing. Stir and modify at 360°C and a rotation speed of 80 r / min for 2 h, cool, and disperse to obtain silicon carbide-coated modified magnesite.
[0051] Among them, the preparation method of silicon carbide-coated modified zirconia includes the following steps: Crush zirconia to obtain a powder with a median particle size of 20 μm; The silicon carbide is the crushed silicon carbide in the preparation method of the above-mentioned silicon carbide-coated modified magnesite; The spinning pitch is the crushed spinning pitch in the preparation method of the above-mentioned silicon carbide-coated modified magnesite. By mass ratio, zirconia:spinning pitch:silicon carbide = 100:3:5. Uniformly mix zirconia and silicon carbide, and then add spinning pitch for uniform mixing. Stir and modify at 360°C and a rotation speed of 100 r / min for 2 h, cool, and disperse to obtain silicon carbide-coated modified zirconia.
[0052] Among them, the mass ratio of silicon carbide blended with phenolic resin liquid is phenolic resin liquid:silicon carbide = 100:10; The median particle size of silicon carbide is 31.7 μm. The median particle size of flake graphite is 8.4 μm. The median particle size of silicon powder is 9.1 μm. The median particle size of boron carbide is 7.5 μm. The particle size range of nano-aluminum oxide is below 200 nm. The diameter range of aluminum titanate fiber is 5 μm to 15 μm, and the length range is 50 μm to 200 μm. The median particle size of zircon powder is 2.8 μm.
[0053] The preparation method of the above-mentioned magnesia-carbon composite refractory brick with thermal shock resistance includes the following steps:
[0054] S1, batching: Mix and prepare the base materials for the inner layer, the middle layer, and the outer layer respectively according to mass parts;
[0055] S2, Pressing: First, fill the inner base material into the mold and press layer by layer. The die head pressure is 260 MPa. After reaching the inner layer thickness, replace the filler with the base material of the middle layer and continue to press layer by layer. The die head pressure is 230 MPa. After reaching the middle layer thickness, replace the filler with the base material of the outer layer and continue to press layer by layer. The die head pressure is 200 MPa. After reaching the brick body thickness, keep the pressure at 200 MPa for 5 minutes to end the pressing and obtain the brick blank.
[0056] S3, Stepwise curing and sintering: Cure the brick blank at 180 °C for 12 h, then heat it up to 600 °C at a rate of 2 °C / min for carbonization for 4 h, and then heat it up to 1450 °C at a rate of 2 °C / min for sintering reaction for 2 h to promote the formation of a dense B-Si-Al-O glass phase from Si + B4C + Al2O3; cool it to obtain the refractory brick.
[0057] Example 3: A thermal shock-resistant magnesia-carbon composite refractory brick. The refractory brick includes a three-layer structure, namely an inner layer, a middle layer, and an outer layer, and the thickness ratio is inner layer: middle layer: outer layer = 1:0.6:1.
[0058] The base material of the inner layer includes the following raw materials in parts by mass: 60 parts of silicon carbide-coated modified magnesia, 15 parts of flake graphite, 2 parts of silicon powder, 2 parts of boron carbide (B4C), 1 part of nano-aluminum oxide (Al2O3), 4 parts of aluminum titanate fiber (Al2TiO5), 2 parts of silicon carbide-coated modified zirconia, and 8 parts of silicon carbide admixed with phenolic resin solution.
[0059] The base material of the middle layer includes the following raw materials in parts by mass: 70 parts of silicon carbide-coated modified magnesia, 11 parts of flake graphite, 2 parts of silicon powder, 2 parts of boron carbide (B4C), 1 part of nano-aluminum oxide (Al2O3), 7 parts of zircon powder (ZrSiO4), 3 parts of aluminum titanate fiber (Al2TiO5), and 9 parts of silicon carbide admixed with phenolic resin solution.
[0060] The base material of the outer layer includes the following raw materials in parts by mass: 80 parts of silicon carbide-coated modified magnesia, 8 parts of flake graphite, 2 parts of silicon powder, 2 parts of boron carbide (B4C), 1 part of nano-aluminum oxide (Al2O3), 4 parts of aluminum titanate fiber (Al2TiO5), and 7 parts of silicon carbide admixed with phenolic resin solution.
[0061] Among them, the preparation method of silicon carbide-coated and modified magnesite includes the following steps: Select dead-burned magnesia with a calcination temperature of 2000 °C as magnesite, and perform particle size grading: particles with a particle size less than 5 mm and greater than or equal to 3 mm account for 25 wt%, particles with a particle size less than 3 mm and greater than or equal to 1 mm account for 35 wt%, particles with a particle size less than 1 mm and greater than or equal to 0.5 mm account for 35 wt%, and particles with a particle size less than 0.5 mm account for 5 wt%; Crush silicon carbide to obtain a powder with a median particle size of 4.6 μm; Crush spinning pitch to obtain a powder with a median particle size of 1.8 μm. By mass ratio, magnesite:spinning pitch:silicon carbide = 100:2:6. Uniformly mix magnesite and silicon carbide, and then add spinning pitch for uniform mixing. Stir and modify at 360 °C and a rotation speed of 150 r / min for 2 h, cool, and disperse to obtain silicon carbide-coated and modified magnesite.
[0062] Among them, the preparation method of silicon carbide-coated and modified zirconia includes the following steps: Crush zirconia to obtain a powder with a median particle size of 23.7 μm; The silicon carbide is the crushed silicon carbide in the preparation method of the above-mentioned silicon carbide-coated and modified magnesite; The spinning pitch is the crushed spinning pitch in the preparation method of the above-mentioned silicon carbide-coated and modified magnesite. By mass ratio, zirconia:spinning pitch:silicon carbide = 100:3:8. Uniformly mix zirconia and silicon carbide, and then add spinning pitch for uniform mixing. Stir and modify at 360 °C and a rotation speed of 200 r / min for 2 h, cool, and disperse to obtain silicon carbide-coated and modified zirconia.
[0063] Among them, the mass ratio of silicon carbide admixed with phenolic resin liquid is phenolic resin liquid:silicon carbide = 100:10; The median particle size of silicon carbide is 30 μm. The median particle size of flake graphite is 16.7 μm. The median particle size of silicon powder is 18.2 μm. The median particle size of boron carbide is 19.5 μm. The particle size range of nano-aluminum oxide is below 200 nm. The diameter range of aluminum titanate fiber is 5 μm to 15 μm, and the length range is 50 μm to 200 μm. The median particle size of zircon powder is 6.0 μm.
[0064] The preparation method of the above-mentioned magnesia-carbon composite refractory brick with thermal shock resistance includes the following steps:
[0065] S1, batching: According to mass parts, respectively mix and prepare the base materials for the inner layer, the middle layer, and the outer layer;
[0066] S2, Compression: First, fill the inner base material into the mold and perform layer-by-layer compaction with a die head pressure of 260 MPa. After reaching the inner layer thickness, replace the filler with the base material for the middle layer and continue layer-by-layer compaction with a die head pressure of 250 MPa. After reaching the middle layer thickness, replace the filler with the base material for the outer layer and continue layer-by-layer compaction with a die head pressure of 200 MPa. After reaching the brick body thickness, maintain a pressure of 230 MPa for 5 minutes to end the compression and obtain a brick blank.
[0067] S3, Segmented Curing and Sintering: Cure the brick blank at 250 °C for 12 h, then heat it up to 600 °C at a rate of 4 °C / min for carbonization for 5 h, and then heat it up to 1550 °C at a rate of 4 °C / min for sintering reaction for 2 h to promote the formation of a dense B-Si-Al-O glass phase from Si + B4C + Al2O3; cool to obtain a refractory brick.
[0068] Example 4: A thermal shock-resistant magnesia-carbon composite refractory brick, the refractory brick includes a three-layer structure, namely an inner layer, a middle layer and an outer layer, and the thickness ratio is inner layer: middle layer: outer layer = 1:0.8:1;
[0069] The base material of the inner layer includes the following raw materials in parts by mass: 65 parts of silicon carbide-coated modified magnesia, 15 parts of flake graphite, 3 parts of silicon powder, 2 parts of boron carbide (B4C), 1.5 parts of nano-aluminum oxide (Al2O3), 4 parts of aluminum titanate fiber (Al2TiO5), 4 parts of silicon carbide-coated modified zirconia, 8 parts of silicon carbide admixed with phenolic resin liquid;
[0070] The base material of the middle layer includes the following raw materials in parts by mass: 75 parts of silicon carbide-coated modified magnesia, 11 parts of flake graphite, 3 parts of silicon powder, 2 parts of boron carbide (B4C), 1.5 parts of nano-aluminum oxide (Al2O3), 7 parts of zircon powder (ZrSiO4), 4 parts of aluminum titanate fiber (Al2TiO5), 9 parts of silicon carbide admixed with phenolic resin liquid;
[0071] The base material of the outer layer includes the following raw materials in parts by mass: 85 parts of silicon carbide-coated modified magnesia, 8 parts of flake graphite, 3 parts of silicon powder, 2 parts of boron carbide (B4C), 1.5 parts of nano-aluminum oxide (Al2O3), 4 parts of aluminum titanate fiber (Al2TiO5), 9 parts of silicon carbide admixed with phenolic resin liquid.
[0072] Among them, the preparation method of silicon carbide-coated and modified magnesite includes the following steps: Select dead-burned magnesia with a calcination temperature of 2000 °C as magnesite, and perform particle size grading: The particles with a particle size less than 5 mm and greater than or equal to 3 mm account for 25 wt%, the particles with a particle size less than 3 mm and greater than or equal to 1 mm account for 35 wt%, the particles with a particle size less than 1 mm and greater than or equal to 0.5 mm account for 30 wt%, and the particles with a particle size less than 0.5 mm account for 10 wt%; Crush silicon carbide to obtain a powder with a median particle size of 3.9 μm; Crush spinning pitch to obtain a powder with a median particle size of 1.5 μm. By mass ratio, magnesite:spinning pitch:silicon carbide = 100:4:6. Uniformly mix magnesite and silicon carbide, and then add spinning pitch for uniform mixing. Stir and modify at 450 °C and a rotation speed of 150 r / min for 4 h, cool, and disperse to obtain silicon carbide-coated and modified magnesite.
[0073] Among them, the preparation method of silicon carbide-coated and modified zirconia includes the following steps: Crush zirconia to obtain a powder with a median particle size of 30 μm; The silicon carbide is the crushed silicon carbide in the preparation method of the above-mentioned silicon carbide-coated and modified magnesite; The spinning pitch is the crushed spinning pitch in the preparation method of the above-mentioned silicon carbide-coated and modified magnesite. By mass ratio, zirconia:spinning pitch:silicon carbide = 100:5:8. Uniformly mix zirconia and silicon carbide, and then add spinning pitch for uniform mixing. Stir and modify at 450 °C and a rotation speed of 200 r / min for 4 h, cool, and disperse to obtain silicon carbide-coated and modified zirconia.
[0074] Among them, the mass ratio of silicon carbide admixed with phenolic resin liquid is phenolic resin liquid:silicon carbide = 100:6; The median particle size of silicon carbide is 52.4 μm. The median particle size of flake graphite is 13.6 μm. The median particle size of silicon powder is 10.4 μm. The median particle size of boron carbide is 11.8 μm. The particle size range of nano-aluminum oxide is below 200 nm. The diameter range of aluminum titanate fiber is 5 μm - 15 μm, and the length range is 50 μm - 200 μm. The median particle size of zircon powder is 5.6 μm.
[0075] The above preparation method of a thermal shock-resistant magnesia-carbon composite refractory brick includes the following steps:
[0076] S1, batching: Mix and prepare the base materials for the inner layer, the base materials for the middle layer, and the base materials for the outer layer respectively according to mass parts;
[0077] S2, pressing: first fill the base material of the inner layer into the mold, and press layer by layer, the die head pressure is 280MPa, after the inner layer thickness is reached, replace the filler with the base material of the middle layer, continue to press layer by layer, the die head pressure is 250MPa, after the middle layer thickness is reached, replace the filler with the base material of the outer layer, continue to press layer by layer, the die head pressure is 230MPa, after the brick body thickness is reached, 230MPa is maintained for 10min, and the pressing is terminated to obtain the brick blank;
[0078] S3, staged solidification and sintering: solidify the brick at 250℃ for 14h, then heat to 700℃ at a rate of 4℃ / min for carbonization for 5h, then heat to 1550℃ at a rate of 4℃ / min for sintering reaction for 2.5h to promote Si+B4C+Al2O3 to form a dense B-Si-Al-O glass phase; cool to obtain refractory bricks.
[0079] Embodiment 5: A thermal shock resistant magnesium-carbon composite refractory brick, the refractory brick comprises a three-layer structure, which is an inner layer, a middle layer and an outer layer in sequence, and the thickness ratio of the inner layer: the middle layer: the outer layer is 1:0.8:0.8;
[0080] The base material of the inner layer includes the following raw materials in parts by mass: 65 parts of silicon carbide coated modified magnesia, 12 parts of flake graphite, 3 parts of silicon powder, 1 part of boron carbide (B4C), 1.5 parts of nano-alumina (Al2O3), 3 parts of aluminum titanate fiber (Al2TiO5), 4 parts of silicon carbide coated modified zirconia, and 6 parts of silicon carbide mixed with phenolic resin liquid;
[0081] The base material of the middle layer includes the following raw materials in parts by mass: 75 parts of silicon carbide coated modified magnesia, 9 parts of flake graphite, 3 parts of silicon powder, 1 part of boron carbide (B4C), 1.5 parts of nano-alumina (Al2O3), 5 parts of zircon powder (ZrSiO4), 4 parts of aluminum titanate fiber (Al2TiO5), and 7 parts of silicon carbide mixed with phenolic resin liquid;
[0082] The base material of the outer layer includes the following raw materials in parts by mass: 85 parts of silicon carbide coated modified magnesia, 5 parts of flake graphite, 3 parts of silicon powder, 1 part of boron carbide (B4C), 1.5 parts of nano-alumina (Al2O3), 3 parts of aluminum titanate fiber (Al2TiO5), and 9 parts of silicon carbide mixed with phenolic resin liquid.
[0083] Among them, the preparation method of silicon carbide-coated modified magnesite includes the following steps: Select dead-burned magnesia with a calcination temperature of 1800°C as magnesite, and perform particle size grading: particles with a particle size less than 5 mm and greater than or equal to 3 mm account for 30 wt%, particles with a particle size less than 3 mm and greater than or equal to 1 mm account for 35 wt%, particles with a particle size less than 1 mm and greater than or equal to 0.5 mm account for 30 wt%, and particles with a particle size less than 0.5 mm account for 5 wt%; Crush silicon carbide to obtain a powder with a median particle size of 4.9 μm; Crush spinning asphalt to obtain a powder with a median particle size of 1.7 μm. According to the mass ratio, magnesite:spinning asphalt:silicon carbide = 100:4:3, uniformly mix magnesite and silicon carbide, and then add spinning asphalt for uniform mixing, stir and modify at 450°C and a rotation speed of 80 r / min for 4 h, cool, and disperse to obtain silicon carbide-coated modified magnesite.
[0084] Among them, the preparation method of silicon carbide-coated modified zirconia includes the following steps: Crush zirconia to obtain a powder with a median particle size of 28.8 μm; The silicon carbide is the crushed silicon carbide in the preparation method of the above-mentioned silicon carbide-coated modified magnesite; The spinning asphalt is the crushed spinning asphalt in the preparation method of the above-mentioned silicon carbide-coated modified magnesite. According to the mass ratio, zirconia:spinning asphalt:silicon carbide = 100:5:5, uniformly mix zirconia and silicon carbide, and then add spinning asphalt for uniform mixing, stir and modify at 450°C and a rotation speed of 100 r / min for 4 h, cool, and disperse to obtain silicon carbide-coated modified zirconia.
[0085] Among them, the mass ratio of silicon carbide admixed with phenolic resin liquid is phenolic resin liquid:silicon carbide = 100:6; The median particle size of silicon carbide is 60 μm. The median particle size of flake graphite is 11.3 μm. The median particle size of silicon powder is 19.4 μm. The median particle size of boron carbide is 18.6 μm. The particle size range of nano-aluminum oxide is below 200 nm. The diameter range of aluminum titanate fiber is 5 μm to 15 μm, and the length range is 50 μm to 200 μm. The median particle size of zircon powder is 2.0 μm.
[0086] The preparation method of the above-mentioned magnesia-carbon composite refractory brick with thermal shock resistance includes the following steps:
[0087] S1, batching: According to the mass parts, respectively mix and prepare the base materials for the inner layer, the base materials for the middle layer and the base materials for the outer layer;
[0088] S2, Compression: First, fill the inner base material into the mold and perform layer-by-layer compaction. The die head pressure is 280 MPa. After reaching the inner layer thickness, replace the filler with the base material for the intermediate layer and continue layer-by-layer compaction. The die head pressure is 230 MPa. After reaching the intermediate layer thickness, replace the filler with the base material for the outer layer and continue layer-by-layer compaction. The die head pressure is 210 MPa. After reaching the brick body thickness, maintain the pressure at 210 MPa for 10 min to end the compression and obtain a brick blank.
[0089] S3, Stepwise Curing and Sintering: Cure the brick blank at 180 °C for 14 h, then heat it up to 700 °C at a rate of 2 °C / min for carbonization for 4 h, and then heat it up to 1450 °C at a rate of 4 °C / min for sintering reaction for 2.5 h to promote the formation of a dense B-Si-Al-O glass phase from Si + B4C + Al2O3; cool it to obtain a refractory brick.
[0090] In the above embodiments, the spinning pitch is from Jining Chenxing Carbon Co., Ltd., with the model CXFS-250; the silicon powder is from Anyang Tianren Metallurgical Refractory Co., Ltd., with a purity of 98%; the phenolic resin is a thermosetting liquid phenolic resin from Jinan Dahui Chemical Technology Co., Ltd., and the curing temperature is 180 °C.
[0091] When the refractory bricks in the above embodiments are used for lining a furnace, the inner layer of the refractory brick faces the furnace cavity, and the outer layer of the refractory brick faces the outer wall of the furnace.
[0092] Comparative Example 1: The base material for the inner layer is replaced with the base material for the intermediate layer; other parameters and methods are the same as in Example 1.
[0093] Comparative Example 2: The base material for the intermediate layer is replaced with the base material for the outer layer; other parameters and methods are the same as in Example 1.
[0094] Comparative Example 3: The silicon carbide-coated modified magnesia is replaced with magnesia, that is, no silicon carbide coating modification is carried out; other parameters and methods are the same as in Example 1.
[0095] Comparative Example 4: The silicon carbide-coated modified zirconia is replaced with zirconia, that is, no silicon carbide coating modification is carried out; other parameters and methods are the same as in Example 1.
[0096] Comparative Example 5: The silicon carbide-doped phenolic resin liquid is replaced with phenolic resin liquid, that is, no silicon carbide is added to the phenolic resin liquid; other parameters and methods are the same as in Example 1.
[0097] Comparative Example 6: No aluminum titanate fiber is added to both the base material for the intermediate layer and the base material for the outer layer; other parameters and methods are the same as in Example 1.
[0098] Comparative Example 7: The silicon carbide-coated magnesia is replaced with magnesia; the silicon carbide-coated zirconia is replaced with zirconia; the silicon carbide admixed with phenolic resin liquid is replaced with phenolic resin liquid; after converting all the silicon carbide used for modification, it is directly admixed into the base material by mass fraction according to the raw materials; other parameters and methods are the same as those in Example 1.
[0099] Comparative Example 8: In the preparation method, the die head pressure during pressing is 200 MPa; variable pressure pressing is not carried out; other parameters and methods are the same as those in Example 1.
[0100] Comparative Example 9: In the preparation method, it is directly heated to 1500 °C at a rate of 5 °C / min and sintered for 2 h, that is, the curing and carbonization heat preservation stages are omitted; other parameters and methods are the same as those in Example 1.
[0101] The refractory bricks of the above examples and comparative examples were made into specimens with a specification of 100 mm × 100 mm × 50 mm for performance testing.
[0102] 1. Bulk density detection: The Archimedes method was used, water immersion, and boiling method for exhaust. The test results are shown in Table 1 below.
[0103] 2. Cold flexural strength detection: Detection was carried out at 25 °C using a universal material testing machine. The test results are shown in Table 1 below.
[0104] 3. High-temperature flexural strength detection: It was heated to 1400 °C at a rate of 15 °C / min and held for 30 minutes, and then the flexural strength was measured. The test results are shown in Table 1 below.
[0105] 4. Thermal shock resistance detection: The specimen was heated to 1300 °C at a heating rate of 10 °C / min and held for 30 minutes, then quickly taken out and put into water at room temperature (25 °C ± 2 °C) for rapid cooling for 3 minutes, so that a large temperature difference was generated on the surface and inside of the specimen to form thermal stress. Such thermal shock cycles were carried out repeatedly. Continuously observe the surface condition of the specimen, and record the number of thermal shock cycles when through cracks appear on the specimen or the spalling amount reaches 10%. The test results are shown in Table 1 below.
[0106] 5. Oxidation resistance detection: The specimen was placed in a high-temperature oxidation furnace, the furnace temperature was set at 1600 °C, and an oxidation atmosphere (oxygen was introduced) was maintained. Under this condition, it was held for 5 hours to allow the specimen to fully react with oxygen. The specimen was taken out and cooled to room temperature naturally. Weigh the specimen, and calculate the mass change rate by comparing with the original mass of the specimen. The test results are shown in Table 1 below.
[0107] 6. Thermal expansion coefficient detection: The specimen was made into a cuboid with dimensions of 50 mm × 10 mm × 10 mm, and heated from room temperature to 1400 °C at a rate of 5 °C / min, and detected using a thermoexpansion instrument. The test results are shown in Table 1 below.
[0108] Table 1 Index Detection Results
[0109]
[0110] As can be seen from the above results, the refractory bricks prepared in Examples 1 to 5 have good service performance, high flexural strength, good thermal shock resistance, and at the same time have good oxidation resistance and anti-expansion properties. They are not prone to cracking and falling off during high-temperature use, and the service life is extended.
[0111] In Comparative Example 1, the inner layer base material was replaced with the intermediate layer base material. The intermediate layer base material mainly plays a role in transition and partial structural support, and its composition and ratio do not match the protection and adaptation requirements of the inner layer for the material layer. The internal structure of the material is unstable, resulting in an increase in pores and a decrease in bulk density. The room-temperature flexural strength decreases due to structural defects; the poor thermal shock resistance is because the thermal stress cannot be effectively buffered; in terms of oxidation resistance, an effective antioxidant barrier cannot be formed, and the mass change rate increases. During high-temperature flexure, the unstable structure is easily damaged and the strength decreases; the coefficient of thermal expansion increases because the internal structure is uneven and the expansion of each part is inconsistent during temperature changes.
[0112] In Comparative Example 2, the intermediate layer base material was replaced with the outer layer base material, lacking the optimized composition ratio and performance characteristics required for the intermediate layer. The overall structural performance of the material is damaged, and the room-temperature flexural strength decreases; the crack propagation cannot be inhibited during the thermal shock process, and the thermal shock resistance decreases; the oxidation resistance is affected by the structural damage, and the mass change rate increases. During high-temperature flexure, due to structural defects, the pressure-bearing capacity weakens; the coefficient of thermal expansion rises because the intermediate transition structure is damaged and the coordination of each layer of the material becomes worse.
[0113] In Comparative Example 3, the silicon carbide-coated modified magnesite was replaced with magnesite. Magnesite is prone to oxidation, resulting in a loose internal structure of the material, an increase in porosity, and a decrease in bulk density. The room-temperature flexural strength, thermal shock resistance, and oxidation resistance all deteriorate sharply. Magnesite softens at high temperatures, and the high-temperature flexural strength decreases significantly; the coefficient of thermal expansion increases because there is no constraint of silicon carbide, and magnesite expands freely to a large extent when the temperature rises.
[0114] In Comparative Example 4, the silicon carbide-coated modified zirconia was replaced with zirconia. The internal defects of the material increase, and it cannot effectively resist thermal stress and oxidation. Zirconia loses the protection of silicon carbide and is prone to participating in reactions to change the crystal structure, including reduction, high-valence oxidation, and subsequent reactions with acidic substances and metal oxides during actual use. The room-temperature flexural strength and thermal shock resistance decrease, and the oxidation resistance deteriorates. At high temperatures, the performance of zirconia deteriorates, and the high-temperature flexural strength decreases; the coefficient of thermal expansion increases because of the lack of the stability enhanced by silicon carbide, and zirconia expands unstably during temperature changes.
[0115] In Comparative Example 5, the silicon carbide-doped phenolic resin liquid was replaced with a phenolic resin liquid. The phenolic resin is prone to decomposition at high temperatures, resulting in a decrease in the internal bonding force of the material and a loose structure; and there is no good filling of silicon carbide after the resin is cured, and the structure is loose. This leads to deterioration of various indicators.
[0116] In Comparative Example 6, no aluminum titanate fibers were added to the intermediate layer and the outer layer base materials. The material could not effectively inhibit crack propagation during the thermal shock process, the thermal shock performance decreased, the structural stability was affected, the cold flexural strength decreased, and the antioxidant performance was also affected to a certain extent. When the high-temperature flexural strength was tested, due to the lack of aluminum titanate fiber reinforcement, the ability to resist the flexural force decreased; the coefficient of thermal expansion increased slightly because the internal reinforcement structure of the material changed and the overall stability deteriorated.
[0117] In Comparative Example 7, a number of key materials were replaced with unmodified raw materials. The material lost the synergistic modification advantage, and the overall performance deteriorated comprehensively; the converted silicon carbide used for all modifications was insufficient according to the raw material addition amount and could not play an effective protective role. The bulk density decreased significantly due to the loose structure; the cold flexural strength, thermal shock resistance, and antioxidant property were much lower than those of the examples. When the high-temperature flexural strength was tested, the material failed rapidly and the strength was extremely low; the coefficient of thermal expansion was extremely large because there was no effective constraint and stable structure inside the material, and each component expanded freely.
[0118] In Comparative Example 8, variable-pressure pressing was not carried out during the pressing process. There were voids and weak interfaces inside the material, and the overall structural strength and stability were affected. The cold flexural strength and thermal shock resistance decreased, and the antioxidant property was affected by the structural defects. When the high-temperature flexural strength was tested, the weak parts were easily damaged and the strength decreased; the coefficient of thermal expansion increased because the structure was not compact and large deformations were easily generated during temperature changes.
[0119] In Comparative Example 9, the curing and carbonization heat preservation stages were omitted. The internal structure of the material was not fully optimized and stabilized, and defects were easily generated during high-temperature sintering. The cold flexural strength, thermal shock resistance, and antioxidant property decreased. When the high-temperature flexural strength was tested, the defects became the source of damage and the strength decreased; the coefficient of thermal expansion increased because the internal structural defects caused the material to expand unevenly during temperature changes.
Claims
1. A heat shock resistant magnesia-carbon composite refractory brick, characterized in that, The refractory brick includes a three-layer structure, which are the inner layer, the middle layer, and the outer layer in sequence, and the thickness ratio is inner layer: middle layer: outer layer = 1:(0.6 - 0.8):(0.8 - 1); The base material of the inner layer includes raw materials in the following mass parts: 60 - 65 parts of silicon carbide-coated modified magnesia, 12 - 15 parts of flake graphite, 2 - 3 parts of silicon powder, 1 - 2 parts of boron carbide, 1 - 1.5 parts of nano-aluminum oxide, 3 - 4 parts of aluminum titanate fiber, 2 - 4 parts of silicon carbide-coated modified zirconia, 6 - 8 parts of silicon carbide admixed phenolic resin liquid; The base material of the middle layer includes raw materials in the following mass parts: 70 - 75 parts of silicon carbide-coated modified magnesia, 9 - 11 parts of flake graphite, 2 - 3 parts of silicon powder, 1 - 2 parts of boron carbide, 1 - 1.5 parts of nano-aluminum oxide, 5 - 7 parts of zircon powder, 3 - 4 parts of aluminum titanate fiber, 7 - 9 parts of silicon carbide admixed phenolic resin liquid; The base material of the outer layer includes raw materials in the following mass parts: 80 - 85 parts of silicon carbide-coated modified magnesia, 5 - 8 parts of flake graphite, 2 - 3 parts of silicon powder, 1 - 2 parts of boron carbide, 1 - 1.5 parts of nano-aluminum oxide, 3 - 4 parts of aluminum titanate fiber, 7 - 9 parts of silicon carbide admixed phenolic resin liquid.
2. The magnesia-carbon composite refractory brick with thermal shock resistance according to claim 1, characterized in that, The preparation method of the silicon carbide-coated modified magnesia includes the following steps: according to the mass ratio, magnesia: spinning pitch: silicon carbide = 100:(2 - 4):(3 - 6), uniformly mix magnesia and silicon carbide, then add spinning pitch for uniform mixing, carry out stirring modification at 360°C - 450°C for 2h - 4h, cool, and break up to obtain silicon carbide-coated modified magnesia.
3. The magnesia-carbon composite refractory brick with thermal shock resistance according to claim 2, characterized in that, The rotation speed of the stirring modification is 80r / min - 150r / min; the magnesia is dead-burned magnesia, and the calcination temperature of the dead-burned magnesia is 1800°C - 2000°C; the particle size distribution of the magnesia is that the particles with a particle size less than 5mm and greater than or equal to 3mm account for 25wt% - 30wt%, the particles with a particle size less than 3mm and greater than or equal to 1mm account for 35wt% - 40wt%, the particles with a particle size less than 1mm and greater than or equal to 0.5mm account for 30wt% - 35wt%, and the particles with a particle size less than 0.5mm account for 5wt% - 10wt%; the median particle size of the silicon carbide is below 5μm; the median particle size of the spinning pitch is below 2μm.
4. A heat shock resistant magnesia-carbon composite refractory brick according to claim 1, characterized in that, The preparation method of the silicon carbide-coated modified zirconia includes the following steps: according to the mass ratio, zirconia: spinning pitch: silicon carbide = 100:(3 - 5):(5 - 8), uniformly mix zirconia and silicon carbide, then add spinning pitch for uniform mixing, carry out stirring modification at 360°C - 450°C for 2h - 4h, cool, and break up to obtain silicon carbide-coated modified zirconia.
5. A heat shock resistant magnesia-carbon composite refractory brick according to claim 4, characterized in that, The rotation speed of the stirring modification is 100r / min - 200r / min; the median particle size of the zirconia is 20μm - 30μm; the median particle size of the silicon carbide is below 5μm; the median particle size of the spinning pitch is below 2μm.
6. The magnesia-carbon composite refractory brick with thermal shock resistance according to claim 1, characterized in that The mass ratio of the silicon carbide admixed phenolic resin liquid is that the phenolic resin liquid:silicon carbide = 100:(6 - 10); the median particle size of the silicon carbide is 30μm - 60μm.
7. The anti-thermal shock magnesia-carbon composite refractory brick according to claim 1, characterized in that, The median particle sizes of the flake graphite, silicon powder, and boron carbide are all below 20μm; the particle size of the nano-aluminum oxide is below 200nm; the diameter range of the aluminum titanate fiber is 5μm - 15μm, and the length range is 50μm - 200μm; the median particle size of the zircon powder is 2μm - 6μm.
8. A preparation method of a thermal shock resistant magnesia-carbon composite refractory brick for preparing the thermal shock resistant magnesia-carbon composite refractory brick according to claim 1, characterized in that, The preparation method includes the following steps: S1, batching: Mix and prepare the base materials for the inner layer, the middle layer, and the outer layer respectively according to mass parts. S2, pressing: First fill the base material for the inner layer into the mold, and carry out layer-by-layer filling and pressing. The die head pressure is 260MPa - 280MPa. After reaching the inner layer thickness, replace the filler with the base material for the middle layer and continue layer-by-layer filling and pressing. The die head pressure is 230MPa - 250MPa. After reaching the middle layer thickness, replace the filler with the base material for the outer layer and continue layer-by-layer filling and pressing. The die head pressure is 200MPa - 230MPa. After reaching the brick body thickness, keep the pressure and end the pressing to obtain a brick blank. S3, sectional curing and sintering: Cure the brick blank at 180℃ - 250℃ for 12h - 14h, then heat up to 600℃ - 700℃ for carbonization for 4h - 5h, then heat up to 1450℃ - 1550℃ for sintering reaction for 2h - 2.5h, and cool to obtain a refractory brick.
9. The preparation method of a thermal shock resistant magnesia-carbon composite refractory brick according to claim 8, characterized in that, In S2, the pressure for keeping the pressure is 200MPa - 230MPa, and the time for keeping the pressure is 5min - 10min.
10. The preparation method of a thermal shock resistant magnesia-carbon composite refractory brick according to claim 8, characterized in that, In S3, the heating rate is 2℃ / min - 4℃ / min.
Citation Information
Patent Citations
Firebrick for ladle and preparation method thereof
CN107963881A
High-strength erosion-resistant low-carbon magnesia carbon brick and preparation method thereof
CN117886617A